Strategy builder how to create and communicate more effective strategies - Cummings, Stephen ca. 20./21. Jh; Angwin, Duncan (Wiley, 2015)
"A visual and interactive guide to building and communicatingstrategies that actually work The effective conditions for selling a strategy are not thatdifferent from a public presentation or a coach seeking to get hisplayers to change tack. For a new approach to succeed you need 'buyin'. Your stakeholders ... bosses, employees, peers, governmentofficials, and investors ... are already making judgments abouthow much they will engage with you and your strategy within sevenseconds of you beginning to explain it. They, and you, are makingstrategic decisions at a glance. So how do you best captivate yourpotential stakeholders in your strategic endeavours? TheStrategy Builder will show you how. Combines a quick guide to key management frameworks with aninteractive "how to adapt the model" approach Includes comments and tweets from experts around the world A visually interactive guide that puts strategy building inperspective "..
Keywords: BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Strategic Planning; Wirtschaft; Strategic planning